Draft Second Five Year Plan of Andaman and Nicobar Islands 1956-61 - Planning Commission (Planning Commission, 1956)
The Andamans and the Nicobars are a string of islands in the Bay of Bengal, stretching over four hundred miles of sea. These Islands are nearer Burma and the East Indies: the distance from Port Blair to Calcutta is 780 miles, to Madras 740 miles, and to Rangoon only 360 miles. Only 92 sea miles separate the southernmost point of Great Nicobar from the northern tip of Sumatra in Indonesia.
Andaman and Nicobar Administration